2019
DOI: 10.1002/jhbp.644
|View full text |Cite
|
Sign up to set email alerts
|

Use of the National Clinical Database to evaluate the association between preoperative liver function and postoperative complications among patients undergoing hepatectomy

Abstract: BackgroundThe aim of the present study was to clarify the association between preoperative liver function and complications after hepatectomy.MethodsThe study included 11,686 patients registered in the National Clinical Database for 2015 for whom data on indocyanine green at 15 min (ICG15) and hepatectomy were available. The patients were divided into four groups: group A (ICG15 <10%; n = 5,661), group B (ICG15 10% to <20%; n = 4,381), group C (ICG15 20% to <30%; n = 1,173) and group D (ICG15 >30%;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…First, there were possible coding errors due to the use of a large nationwide database. Second, several indicators related to the liver functional reserve, such as liver resection rates calculated by CT volumetry, K value of indocyanine green test, and other liver function tests, were missing 50,51 . Third, the long‐term outcomes could not be analyzed because the NCD does not include any survival data.…”
Section: Discussionmentioning
confidence: 99%
“…First, there were possible coding errors due to the use of a large nationwide database. Second, several indicators related to the liver functional reserve, such as liver resection rates calculated by CT volumetry, K value of indocyanine green test, and other liver function tests, were missing 50,51 . Third, the long‐term outcomes could not be analyzed because the NCD does not include any survival data.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis using data from the national database also showed that an increase in the volume of blood loss and a lengthened operation time were risk factors for > CDIII complications. 29 These intraoperative factors are affected by the large size and aggressive nature of the tumor, and the fact that they require radical treatment; therefore, they would be confounded with preoperative patient and tumor factors. Postoperative factors such as a high bilirubin concentration in the abdominal drain indicate that bile leakage had already occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Liver resection with broad exposure of the hilar Glissonean sheath is considered as a high‐risk procedure 27 that may lead to bile leakage. In addition, several studies have considered intraoperative and postoperative factors as the risk factors for bile leakage 3,28,29 . An analysis using data from the national database also showed that an increase in the volume of blood loss and a lengthened operation time were risk factors for > CDIII complications 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermittent clamping of the hepatoduodenal pedicle using Pringle's maneuver has decreased intraoperative hemorrhage [3], and perioperative steroid administration has lowered postoperative serum bilirubin levels [4]. However, postoperative complications remain a major problem, occurring in 36% (25-49%) of cases [5][6][7][8][9][10][11][12]. The 5year recurrence rate of patients who have undergone curative resection of HCC is over 70% [13], and reducing early post-treatment recurrence will be key to the treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%